Polytempo. Proportions, interrelations and trinity of tempos - Dragostinov, Stefan (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
This work analyzes the tempo proportions of three simultaneously going tempo lines (tempos) â€“ 72 MM, 78 MM, 84 MM â€“ in the cantata â€žThe Fairâ€ (â€žLa Foireâ€) by Stefan Dragostinov. The first performance of this work was on 9th September 1978 in Hilversum, Holland, in WARA studios, at the time of the The Gaudeamus International Composers Award; it was performed by three female chamber formations of the National Radio Holland, each with a different conductor and the whole work conducted by prof. Hans Muller. The cantata â€žThe Fairâ€œ by Stefan Dragostinov was awarded the first prize of the Gaudeamus International Prize for Composers in 1978.